INFANTILE TREMOR SYNDROME IN CHILDREN AND MATERNAL VITAMIN B12 DEFICIENCY: A TIME FOR PRIMARY PROPHYLAXIS - MAURYA, MANISHA; MAURYA, ARUN KUMAR; MISHRA, NANDITA; SINGH, MUKESH VIR; SHUKLA, SANTOSH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to determine the percentage of Vitamin B12 deficiency in mothers of children suffering from infantile tremor syndrome (ITS). Other objectives were to determine the percentage of Vitamin B12 deficiency in children and to look for percentage of children having neurological changes in contrast enhanced computed tomography (CT) scan of brain. Methods: Data of children between 1 and 60 months admitted between April 2019 and December 2019 with ITS in a tertiary care hospital were collected. Serum Vitamin B12 levels of both mother and child were determined. Vitamin B12 deficiency and insufficiency were defined as levels <200 pg/ mL and 200–350 pg/mL, respectively. The primary outcome was percentage of mother with Vitamin B12 deficiency and the secondary outcomes were percentage of children with Vitamin B12 deficiency and percentage of children with cerebral atrophy on contrast-enhanced CT of brain. Results: Forty-five children were enrolled in our study. Vitamin B12 deficiency was found in 29 (64.4%) children and 22 (55%) of their mothers. Cerebral atrophy in CT scan was found in 29 (70%) out of 41 children. Conclusion: The most of the mothers of children with ITS are also Vitamin B12 deficient. ITS occurs in infants and toddler with underlying Vitamin B12 deficiency and causes early cerebral atrophy in children, which is crucial period of brain growth. Hence, screening and supplementing anemic pregnant women with vitamin B12 can be one of the primary prevention in India.